Do Neurocognitive SCAT3 Baseline Test Scores Differ Between Footballers (Soccer) Living With and Without Disability? A Cross-Sectional Study. Issue 1 (January 2018) - Weiler, Richard; van Mechelen, Willem; Fuller, Colin; Ahmed, Osman Hassan; Verhagen, Evert
Abstract : Objective: To determine if baseline Sport Concussion Assessment Tool, third Edition (SCAT3) scores differ between athletes with and without disability. Design: Cross-sectional comparison of preseason baseline SCAT3 scores for a range of England international footballers. Setting: Team doctors and physiotherapists supporting England football teams recorded players' SCAT 3 baseline tests from August 1, 2013 to July 31, 2014. Participants: A convenience sample of 249 England footballers, of whom 185 were players without disability (male: 119; female: 66) and 64 were players with disability (male learning disability: 17; male cerebral palsy: 28; male blind: 10; female deaf: 9). Assessment and Outcome Measures: Between-group comparisons of median SCAT3 total and section scores were made using nonparametric Mann–Whitney–Wilcoxon ranked-sum test. Main Results: All footballers with disability scored higher symptom severity scores compared with male players without disability. Male footballers with learning disability demonstrated no significant difference in the total number of symptoms, but recorded significantly lower scores on immediate memory and delayed recall compared with male players without disability. Male blind footballers' scored significantly higher for total concentration and delayed recall, and male footballers with cerebral palsy scored significantly higher on balance testing and immediate memory, when compared with male players without disability. Female footballers with deafness scored significantly higher for total concentration and balance testing than female footballers without disability. Conclusions: This study suggests that significant differences exist between SCAT3 baseline section scores for footballers with and without disability. Concussion consensus guidelines should recognize these differences and produce guidelines that are specific for the growing number of athletes living with disability.